Ten years of experience and progress of electronic immunization registry system in Jiangsu Province, China - Guodong Kang; Minghao Zhou; Zhiguo Wang; Jing Yu; Fenyang Tang (Taylor & Francis Group, 2018)
The electronic immunization registry system (EIRs) can improve the vaccine coverage monitoring significantly. The EIRs in Jiangsu Province, China was set up since 2006. In this paper, the mechanism and structure of the EIRs were summarized, and then some function of this system were illustrated. The application of the EIRs was believed to be an effective health management and electronic vaccine record quality improvement tool in China. The experience and progress we gained could provide a valuable example for other countries.